Implementasi Business Model Canvas dalam Rangka Meningkatkan Profesionalisme Bisnis Mahasiswa - Fristiani, Nosilia; Sari, Retno Murni (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to provide education and assistance in preparing Business Model Canvas (BMC) to students who already have businesses. The needs of students who already have businesses and will understand structured business models as a basis for sustainable business development. Although many students have started businesses, most do not fully understand the important elements in business summarized in the Business Model Canvas (BMC) method. The implementation method of this service includes the stage of identifying participants' businesses, providing material on the concept and elements of BMC, group discussions, and direct practice of preparing BMC methods based on each student's business. This activity was attended by a number of students with various business backgrounds, ranging from culinary, fashion, camping equipment rental, to digital services. An educational and participatory approach was used so that students not only understand the concept, but are also able to apply it in their real business. The results of the activity showed that participants were able to understand their business structure more systematically and find potential business development that had not previously been mapped. Education on the Business Model Canvas (BMC) method also encourages students to think more strategically and focused in planning the sustainability of their businesses.